The Impact of Poverty in the Implementation of Play-Based Pedagogy in Early Childhood Education in Mutare Rural - Cosmas Muchandiona; Emilda Rumbidzai Machiridza; Fortunate Mwaruta (South Sulawesi Education Development (SSED), 2026)
Purpose: This qualitative study investigates how poverty impacts the implementation of play-based pedagogy (PBP) in Early Childhood Education (ECE) centres in Mutare Rural, Zimbabwe. While PBP is globally recommended as a developmentally appropriate practice, its feasibility in low-resource, rural contexts remains critically under-researched. This study addresses this gap by examining the specific barriers poverty creates, the adaptive strategies educators employ and how socio-economic deprivation shapes the nature of children's learning. Methodology: Data were collected through semi-structured interviews with 5 ECE educators, focus group discussions with 20 caregivers and systematic observations across ten purposively selected ECE centres. Thematic analysis revealed that poverty fundamentally reconfigures PBP from a child-centred, exploratory ideal into a practice of 'survivalist adaptation Results: Key findings show that severe material scarcity and infrastructur al deficits create 'pedagogical deserts,' while chronic child hunger directly impairs the cognitive energy necessary for engagement. In response, ECE educators engage in exhausting, unsupported labour, improvising with local materials and indigenous games in a process of 'innovation by desperation.' Conclusions: The study concludes that poverty does not merely weaken PBP but actively produces an alternative, constrained pedagogy. It argues for an integrated policy response that combines material support, context-specific teacher training in low-resource PBP and the formal curricular integration of indigenous play practices to foster sustainable and equitable early learning.